1998
DOI: 10.2165/00002018-199819060-00001
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs and Cognitive Function

Abstract: Studies suggest that high dose NSAID use may be associated with a reversible impairment of cognition in the elderly. Prolonged NSAID use, on the other hand, may prevent the decline in cognition associated with aging. However, it has yet to be to be definitively determined whether this protection arises from an anti-inflammatory effect that modifies pathways involved in Alzheimer's dementia, or is mediated by a platelet effect that decreases the risk of cerebrovascular disease. Further large-scale, randomised, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…For example, it is conceivable that cognitive side-effects could have been identified as conversion to AD rather than an adverse event, so the absence of a clear difference between rofecoxib and placebo for reported NSAID-type CNS adverse events is inconclusive. Some studies which were specifically designed to assess cognition in normal elderly subjects receiving NSAIDs did find evidence for detrimental effects [34], although as yet no adequately powered randomized controlled trial has been performed to investigate this.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is conceivable that cognitive side-effects could have been identified as conversion to AD rather than an adverse event, so the absence of a clear difference between rofecoxib and placebo for reported NSAID-type CNS adverse events is inconclusive. Some studies which were specifically designed to assess cognition in normal elderly subjects receiving NSAIDs did find evidence for detrimental effects [34], although as yet no adequately powered randomized controlled trial has been performed to investigate this.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced prevalence of Alzheimer's disease has been found among patients with arthritis (McGeer et al, 1996). A reduced risk of Alzheimer's disease has also been observed among users of aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) (Stewart et al, 1997;Karplus and Saag, 1998). A clinical study with indomethacin showed some sign for arrest in decline of mental function of treated Alzheimer patients (Rogers et al, 1993) and presently several clinical trials with anti-inflammatory drugs are ongoing.…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…A Swedish population-based study on individuals 80 years old or more revealed users of high-dose (>500 mg/day) aspirin had significantly lower prevalence of Alzheimer's dementia whereas users of 75 mg daily dose had only numerical but insignificant reduction of Alzheimer's dementia, even after correction of stroke, transient ischemic attack, myocardial infarction, angina pectoris, and congestive heart failure [15]. In some studies examining dosage effects, elderly persons who took high-dose NSAIDs got poorer memory and decline faster than those taking low doses [26]. Another case control study involving subjects with average age of 81 disclosed that not only a high-dose (>1000 mg/day) anti-inflammatory action of aspirin but also low-dose antiplatelet action (<500 mg/day) is protective against Alzheimer's dementia [9].…”
Section: Discussionmentioning
confidence: 99%